2000
DOI: 10.1046/j.1529-8027.2000.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on peripheral nerve function and regeneration

Abstract: Aging deeply influences several morphologic and functional features of the peripheral nervous system (PNS). Morphologic studies have reported a loss of myelinated and unmyelinated nerve fibers in elderly subjects, and several abnormalities involving myelinated fibers, such as demyelination, remyelination and myelin balloon figures. The deterioration of myelin sheaths during aging may be due to a decrease in the expression of the major myelin proteins (P0, PMP22, MBP). Axonal atrophy, frequently seen in aged ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
270
1
10

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 602 publications
(302 citation statements)
references
References 124 publications
21
270
1
10
Order By: Relevance
“…Engaging several methods, we set out to comprehensively describe age‐dependent changes on functional, structural, cellular, and molecular levels. Our experimental design confirmed and further detailed previous work in this area (Figures 1 and 2) (He, Yadgarov, Sharif, & McCluskey, 2012; Painter et al, 2014; Scheib & Hoke, 2016; Verdu et al, 2000). …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Engaging several methods, we set out to comprehensively describe age‐dependent changes on functional, structural, cellular, and molecular levels. Our experimental design confirmed and further detailed previous work in this area (Figures 1 and 2) (He, Yadgarov, Sharif, & McCluskey, 2012; Painter et al, 2014; Scheib & Hoke, 2016; Verdu et al, 2000). …”
Section: Discussionsupporting
confidence: 89%
“…A growing body of work demonstrates age‐dependent decline of peripheral nerve regeneration capacity (Painter et al, 2014; Verdu et al, 2000; Wang et al, 2007), but insight into underlying mechanisms remains limited. To better understand age‐dependent factors impacting on peripheral nerve regeneration, we performed sciatic nerve crush injuries on C57BL/6 J mice of two different ages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some debate in the literature about the occurrence of physiological alteration in the processing of nociception and pain, which can be ascribed to age [2,40,41]. It is clearly evident that there is a high prevalence of chronic pain in the elderly, and this can be attributed partly to the physiological changes of peripheral and central [38]; pain mechanisms and to changes in some psychological attitudes towards pain [41]. It has been reported that changes in sensations and perceptions in sensory systems occur in the elderly [42].…”
Section: Physiological Changes With Agingmentioning
confidence: 99%
“…A large amount of the literature on the neurobiology of aging suggests that there is a widespread and considerable alteration in the structure, function, and biochemistry of the peripheral [13,37,38] and central nervous system [13] structures of older individuals. It has been documented that there is a decrease in the density of myelinated fibres with aging [43 -45].…”
Section: Physiological Changes With Agingmentioning
confidence: 99%